Image of intestinal parasites on muscomorpha as mechanical vectors at Pasar Inpres Tanjung Morawa - Puja Fatimah; Adelina Haryani Sinambela (Institute of Computer Science (IOCS), 2023)
The morphology of flies is a hairy body with a pair of wings and three pairs of legs equipped with a pair of pulviculus. Pulviculus serves as a stick for flies on the surface of objects, so that microorganisms and parasites can stick or be carried by flies. Muscomorpha is the most common fly found in the community with the support of its morphology and ability to fly to help its role as a mechanical vector of various pathogens, one of which is intestinal parasites. This study is to determine the picture of intestinal parasites in Muscomorpha at the Tanjung Morawa Inpres Market in 2023. This study is a descriptive study with a cross sectional design and uses primary data obtained from fly catching with fly traps and examination of samples at the Parasitology Laboratory, Faculty of Medicine, University of North Sumatra. The sample used was Muscomorpha caught with a fly trap at the Inpres Market of Tanjung Morawa B Village, Tanjung Morawa District, Deli Serdang Regency. The results of this study were Muscomorpha found are Musca domestica and Chrysomya megacephala and in Muscomorpha found intestinal parasites in the form of Ascaris lumbricoides eggs 14 pieces (48.28%), Hookworm eggs 8 pieces (27.59%) and Trichuris trichiura eggs 7 pieces (24.13 %). The conclusion of this study was that intestinal parasites were found in the form of 14 Ascaris lumbricoides eggs (48.28%), 8 Hookworm eggs (27.59%) and 7 Trichuris trichiura eggs (24.13%).